The Effect of Brand Image on Purchase Decision of Scarlett Cosmetics Mediated by Brand Ambassador - Putri, Galih Widya; Juliati, Ratih; Fitriasari, Fika (Jurnal Manajemen Bisnis dan Kewirausahaan, 2023)
This study aims to determine and analyze the influence of brand image on purchasing decisions mediated by brand ambassadors. This research was conducted at the official Scarlett cosmetic store located in Malang City totaling 120 respondents. This study uses a non-probability sampling technique with purposive sampling. Data collection techniques using a questionnaire and analyzed with Smart-PLS. This study found that brand image has a positive and significant effect on purchasing decisions, brand ambassadors have a positive and significant effect on purchasing decisions, brand image has a positive and significant effect on brand ambassadors and brand ambassadors mediate brand image on purchasing decisions.